A compound silica-trifluoroacetyl powder for fire suppressant: Preparation, characterization and suppression mechanism discussion. (July 2020) - Fan, Rujia; Jiang, Yong; Qiu, Rong
Abstract: This paper reported the preparation, fire suppression efficiency, and suppression mechanism of a new suppression powder. In present work, the new suppressant was designed for combining the ability of terminating the chain reactions into the powder extinguishing agent. The trifluoroacetyl group (COCF3 ) was grafted onto the silicon dioxide (SiO2 ), and called the compound SiO2 –F. Several tests for characterizing the structure and morphology of the compound powder were done. The results indicated that the powder was prepared successfully. Then, the burning velocity of methane-air flame with powder addition and minimum extinguishing concentration were measured to evaluate the fire suppression efficiency. In comparison with NaHCO3 and SiO2 powders, the SiO2 –F powder had more pronounced fire suppression efficiency. Furthermore, the fire suppression mechanism of the powder was systematically studied. The physical and chemical suppression mechanisms worked together to suppress the flame. The physical suppression mainly stemmed from the heat absorption of solid substances, and occupied 23.1% of the total suppression effect. The chemical suppression was mainly due to the termination of chain reactions by the fluorinated species which were released when the powder was exposed to high temperature.